Describing the linkage between administrative social assistance and health care databases in Ontario, Canada - Claire de Oliveira; Evgenia Gatov; Laura Rosella; Simon Chen; Rachel Strauss; Mahmoud Azimaee; Elizabeth Paterno; Astrid Guttmann; Ministry of Children, Community and Social Services-ICES Working Group; Nelson Chong; Peter Ionescu; Sean Ji; et al. (International Journal of Population Data Science, 2022)
Background The linkage of records across administrative databases has become a powerful tool to increase information available to undertake research and analytics in a privacy protective manner.